Optimalisasi Inventaris Pada Perusahaan Perkebunan Sawit PT. Bahruny Di Kuala Besilam, Tanjung Pura - Alfred J. Sianipar; Rusmini; Irwin Niko WP. Hutapea; Andiyamin (Arsil Media, 2024)
The purpose of this community service is to enhance understanding and knowledge among employees regarding the management and recording of existing asset conditions up to reporting, and to create added value in managing company property in a more orderly, accountable, and transparent manner, as well as the use of supporting technology in conducting company inventory, particularly at PT. Bahruny Kuala Besilam, Tanjung Pura, Langkat Regency, North Sumatra Province. The materials to be presented in this community service are: governance, effectiveness, and efficiency in optimizing company inventory. This is related to enhancing and creating added value in managing company property as a support for data completeness planning activities in realizing program planning activities at PT. Bahruny Kuala Besilam, Tanjung Pura, Langkat Regency, North Sumatra Province. From this community service, it is evident that there has been an improvement in the understanding of PT. Bahruny Kuala Besilam, Tanjung Pura employees regarding the more orderly, accountable, and transparent management and recording of asset conditions in the company's asset records.